2017
DOI: 10.1083/jcb.201610093
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis HAP2/GCS1 is a gamete fusion protein homologous to somatic and viral fusogens

Abstract: HAP2/GCS1 is essential for gamete fusion in plants, invertebrates, and protists. Valansi et al. demonstrate that a plant HAP2 is an authentic fusion protein that can fuse animal cells.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
160
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(166 citation statements)
references
References 46 publications
4
160
1
1
Order By: Relevance
“…A stem region connects these globular domains to two transmembrane domains in flaviviruses 8 or a single-pass transmembrane domain and a cytoplasmic domain in eukaryotes. Although sequence homology is not detectable among class II fusogens from different virus families or with HAP2, similar three-dimensional structures and functions suggest that they diverged from a common ancestor [3][4][5] . As with viral class II proteins, HAP2 functions uni-directionally.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A stem region connects these globular domains to two transmembrane domains in flaviviruses 8 or a single-pass transmembrane domain and a cytoplasmic domain in eukaryotes. Although sequence homology is not detectable among class II fusogens from different virus families or with HAP2, similar three-dimensional structures and functions suggest that they diverged from a common ancestor [3][4][5] . As with viral class II proteins, HAP2 functions uni-directionally.…”
Section: Introductionmentioning
confidence: 92%
“…Recent work on HAP2 from the green alga Chlamydomonas, the flowering plant Arabidopsis, and the ciliate Tetrahymena shows that HAP2 is, in common with fusogens used by certain enveloped viruses to enter host cells, a class II fusion glycoprotein [3][4][5] . Class II fusogens are characterized by their mainly β -sheet-containing-domains I, II, and III (referred to here as D1, D2, and D3) 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these proteins become eliminated from the plasma membrane after gamete fusion, and this process correlates with a reduction in the fusogenic capacity of the gametic cell so as to prevent polygamy (Liu et al, ). Also in flowering plants, HAP2/GCS1 has been reported to be an essential sperm component required for gamete fusion (Mori et al, ; Valansi et al, ; von Besser et al, ). The corresponding egg cell plasma membrane localized factor that is essential for the gamete fusion is not yet known but we speculate that similar mechanisms might operate as well in flowering plants.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding to GCS1/HAP2, it has been reported that GCS1/HAP2 is homologous to viral class II fusion protein (Fédry et al 2017;Pinello et al 2017;Valansi et al 2017). To achieve somatic cell fusion of mammalian cells, ectopic expression of Arabidopsis GCS1/HAP2 was required for both cells, indicating bilateral homotypic mechanism of GCS1/HAP2.…”
mentioning
confidence: 99%
“…To achieve somatic cell fusion of mammalian cells, ectopic expression of Arabidopsis GCS1/HAP2 was required for both cells, indicating bilateral homotypic mechanism of GCS1/HAP2. Since GCS1/HAP in flowering plants is specific to male gametes, it has been hypothesized that female gametes express a GCS1/HAP2 family protein that interacts with sperm GCS1/HAP2 as the bilateral mechanism for fertilization (Valansi et al 2017). When a secretory-type GCS1/HAP2 (named GAH), in which the single transmembrane region of GCS1/ HAP2 was replaced by GFP, was ectopically expressed in Arabidopsis egg cell, occasional blockade of double fertilization was observed (Mori 2014).…”
mentioning
confidence: 99%